2020
DOI: 10.1007/s11916-020-00892-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Headache in Children and Adolescents—Another Type of Pandemia

Abstract: Purpose of Review Headaches are not only responsible for restrictions in everyday life in adults. In children and adolescents, regular headaches lead also to reduced life quality and limitations in the social sphere, in school education, and in professional careers. Here, we provide an overview on the frequency of headache in children and adolescents with the aim of increasing awareness about this particular health issue. Recent Findings Overall, headache prevalence in children and adolescents has been incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 49 publications
1
33
1
1
Order By: Relevance
“…Finally, some argue that migraine and episodic TTH in childhood are both part of the same headache syndrome or, more precisely, two ends of the same continuum [ 8 , 24 , 25 ]. This “continuum theory” of headache is also supported by those children and adolescents who present clinically with “mixed headache syndrome,” meaning a combination of TTH and migraine (mostly without aura).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some argue that migraine and episodic TTH in childhood are both part of the same headache syndrome or, more precisely, two ends of the same continuum [ 8 , 24 , 25 ]. This “continuum theory” of headache is also supported by those children and adolescents who present clinically with “mixed headache syndrome,” meaning a combination of TTH and migraine (mostly without aura).…”
Section: Discussionmentioning
confidence: 99%
“…Care services for children and adolescents with headaches are yet to meet the needs required, and lack of or late pediatric headache management increases their burden on children and their families. Several studies have addressed the prevalence of pediatric and juvenile headaches, which has indeed been increasing in the last years ( 14 ). However, these studies remain scarce worldwide, especially among the pediatric and adolescent age groups; in particular, the Arab world, including Kuwait, are falling short in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…The overall one-year prevalence of headache in India is 64% [1]. School-based cross-sectional studies worldwide have reported a headache prevalence of about 20% in younger children, and up to 88% in adolescents [2,3]. Children with headache have a lower health-related quality of life, and suffer a more significant impact on their education, due to school absenteeism and poor scholastic performance [2].…”
Section: Introductionmentioning
confidence: 99%